KARAKTERISASI SIFAT FISIKOKIMIA TEPUNG TALAS BENENG SEBAGAI PANGAN KHAS KABUPATEN PANDEGLANG - Septariawulan Kusumasari; Fitria Riany Eris; Sri Mulyati; Vega Yoesepa Pamela (Jurnal Agroekoteknologi, 2019)
ABSTRACTTalas beneng is indigenous food from Pandeglang that had potential to be alternative carbohydrate source beside wheat flour. The aim of this study was to characterize physical and chemical properties of flour from Talas beneng. Physical properties this flour had L 91.13, a 2.75, b 11.27, and white degree 68.56%. This flour had brownish color. The result of chemical properties showed that water content, ash, fat, protein, carbohydrate, starch, amylose, and amylopectin respectively 9.04%, 2.25%, 0.17%, 6.73%, 81.81%, 56.29%, 19.27%, and 37.02%. Beneng taro flour could be made product that need low protein flour such as cookies, crackers, brownies, waffle, crepes, or pancake.